THE USE OF SWEAR WORDS IN ONLINE COMMUNICATION: A GENDER-BASED STUDY AMONG UNIVERSITY STUDENTS - Ni Ketut Putri Nila Sudewi; Komang Satria Wirasa (Universitas Putera Batam, 2026)
This study investigated gender differences in the use of swear words in online communication among university students. The research focused on identifying differences in frequency, context, types, and language choice of swear word usage between male and female students. The study employed a mixed-method approach. Quantitative data were collected through questionnaires to 40 students from the English Literature Department at Universitas Bumigora. Meanwhile, qualitative data from open-ended responses and follow-up interviews were analyzed using thematic analysis. The findings revealed that male students used swear words more frequently and in a wider range of contexts, particularly in joking and social interaction. In contrast, female students used swear words less frequently and tended to use them mainly to express surprise or emotions in more controlled or modified forms. The study also found that both groups used multilingual expressions, although female students showed a stronger preference for mixed-language usage. These findings indicated that gender differences in language use were still evident but were becoming more flexible in digital communication.